Peningkatan Kemampuan Membaca Kitab Kuning Dengan Metode Arba’in Berbantu Media PowerPoint - Sodikin, Ahmad; Hasan, Sholeh; Romdloni (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Kitab Kuning is one of the primary sources in Islamic education, and it contains the teachings of Islam and Islamic law. However, the traditional methods used in Islamic boarding schools often do not effectively facilitate the understanding and mastery of the kitab kuning. The main objective of this research is to improve the ability to read kitab kuning through the application of the Arba'in method, which is assisted by Interactive PowerPoint media. This research also aims to measure the effectiveness of this method in helping students understand and master the kitab kuning. The research approach used is qualitative, while the research type is a case study, with data collection techniques including interviews, observations, and documentation. This research is expected to produce a more effective learning method in improving the ability to read the kitab kuning in Islamic boarding schools. The results of the research: The process is then continued by guided memorization of page 1 by the teacher, which has been read and explained, and uploaded on Facebook to be watched by parents, teachers, and friends. In the evaluation stage, students practice reading the kitab kuning in front of the teacher and answer some questions posed. The effectiveness of using the Arba'in method assisted a success rate of 85% among students or alumni of Nurul Huda 2 High School. Meanwhile, kitab kuning learning using the Arba'in method among students at the junior and senior high school levels achieved a success rate of 50%, attributed to constraints in electronic and social media for depositing memorization results from learning.